PENILAIAN KESEHATAN KEUANGAN PADA PERUSAHAAN ASURANSI UMUM - Agus Riyanto; Siti Rohmah; Sri Wahyuti; Sugiarto Sugiarto (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2025)
The purpose of this study is to see the health of general insurance companies by calculating Risk Based Capital, where Risk Based Capital is a measurement of the health of the insurance company's finances by calculating the amount of permitted assets minus permitted liabilities and dividing it by the Minimum Risk Based Capital (MMBR). Minimum Risk Based Capital is the total funds needed to maintain losses that will occur due to deviations or violations when assets and liabilities are managed. From a population of 18 insurance companies, 13 general insurance companies were selected. From the results of the analysis, it is known that general insurance companies listed on the Indonesia Stock Exchange are in very healthy, healthy, and fairly healthy conditions, as evidenced by the solvency ratio or health level of each general insurance company being above 120%, which means that the company's obligations are well met.